In vitro study of antioxidant activity of lactic acid bacterial strains isolated from Algerian fermented products - Nabila Benhamada; Ouahiba Benhamada; Sara Mellit; Imène Moussaoui; Tayeb Idoui (Acta Scientiarum. Biological Sciences, 2025)
The aim of this study was to evaluate the antioxidant activity of 17 strains of lactic acid bacteria isolated from traditionally fermented durum wheat. In vitro tests were caried out: resistance to hydrogen peroxide, total phenolic compounds, DPPH and superoxide anion radicals scavenging assay, and finally, ferric reducing antioxidant power. The greatest resistance to hydrogen peroxide was observed in LS09, LS10, and LS17 strains. Among these three strains, the highest content of phenolic compounds was registered in LS17, this strain presented also the highest reducing power activity. Furthermore, the highest ability to scavenge the DPPH radical was observed in LS10, to scavenge superoxide anion radical was in LS09. Moreover, the use of natural antioxidant can be used in food processing to limit the use of chemical antioxidants.